Locus of Control, Independensi, dan Audit Tenure sebagai Faktor Penentu Kualitas Audit - Pronosokodewo, Baniady Gennody; Tkela, Melianus E.; Permatasari, Vitta Dwi (Universitas PGRI Yogyakarta, 2025)
This research aims to examine the effect of locus of control, independence, and audit tenure on audit quality. The population in this study is a Public Accounting Firm (KAP) in Yogyakarta. The sample in this study were 62 respondents who were external auditors at the Yogyakarta KAP. The sampling technique was determined by the snowball sampling method. The analytical method uses: descriptive statistics, qualitative data testing and hypothesis testing. The results of this study indicate that locus of control, independence, and audit tenure have a positive significant on audit quality.